2010
DOI: 10.1590/s1517-83822010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characteristics of lactic acid bacteria isolated from ripe mulberries in Taiwan

Abstract: The objective of this study was to isolate, characterize, and identify lactic acid bacteria (LAB) from ripe mulberries collected in Taiwan. Ripe mulberry samples were collected at five mulberry farms, located in different counties of Taiwan. Eighty-eight acid-producing cultures were isolated from these samples, and isolates were divided into classes first by phenotype, then into groups by restriction fragment length polymorphism (RFLP) analysis and sequencing of 16S ribosomal DNA (rDNA). Phenotypic and biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
(20 reference statements)
1
25
1
Order By: Relevance
“…The presence of genotypically identified representatives of species of the genera Enterococcus, Streptococcus and Lactobacillus in isolates from plants of different origins have been reported by other authors (Hartnett et al 2002;Magnusson et al 2003;Michaylova et al 2007;Chen et al 2010;Baradaran et al 2012). Hartnett et al (2002) identified E. faecium in isolates from raw barley; in isolates from sorghum, defined species Enterococcus mundtii and E. faecalis were found-which were undetected in plant isolates that we examined-as well as Lactococcus lactis in isolates from raw barley.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…The presence of genotypically identified representatives of species of the genera Enterococcus, Streptococcus and Lactobacillus in isolates from plants of different origins have been reported by other authors (Hartnett et al 2002;Magnusson et al 2003;Michaylova et al 2007;Chen et al 2010;Baradaran et al 2012). Hartnett et al (2002) identified E. faecium in isolates from raw barley; in isolates from sorghum, defined species Enterococcus mundtii and E. faecalis were found-which were undetected in plant isolates that we examined-as well as Lactococcus lactis in isolates from raw barley.…”
supporting
confidence: 62%
“…As such, genotype-based methods such as 16S rDNA represent a valuable addition to phenotypic methods for precise identification of lactobacteria isolated from certain microbial communities (Kostinek et al 2007;Tanasupawat et al 2007;Chen et al 2010;Kpikpi et al 2010;Venturi et al 2012;Baradaran et al 2012;Alemayehu et al 2014). Despite the widespread use of LAB, each plant habitat is characterized by a specific microbocenosis with unique biological activity.…”
Section: Identification Of Lactic Acid Bacteria By Pcr and Constructimentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that each of these strains encodes a bacteriocin identical to weissellicin 110. It is interesting that these independent strains isolated from different fermented foods and geographical locations (14,19). However, the role of these weissellicin 110 producing W. cibaria strains in the fermented foods or the related vegetables remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Besides W. cibaira 860106, strain W. cibaria 110 (8) was used as the positive control. Strains W. hellenica 4-7 (weissellicin L producer) (11) and W. cibaira I042209 and I042210 (no bacteriocin-producing ability) (19) were used as the negative controls.…”
Section: Weissellicin 110 Gene-specific Pcrmentioning
confidence: 99%